2004
DOI: 10.1159/000081660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saliva Composition on Experimental Root Caries

Abstract: The aim of this study was to determine the effect of saliva composition on caries lesion development independently of the flow rate of unstimulated whole saliva (UWS) and other caries-related variables such as lesion progression time, oral hygiene level, and fluoride exposure. We hypothesized that this could be done by developing experimental root caries under carefully controlled conditions in situ in test subjects with UWS flow rates within a narrow window of normalcy. Fifteen female and 5 male subjects (66 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 44 publications
(32 reference statements)
1
18
0
10
Order By: Relevance
“…Our results showed that increasing age and high dental plaque scores, as well as decreasing unstimulated flow rates were highly associated with increasing DMFS values, whereas no association was found with the level of HbA1c. These data confirm the existing knowledge about dental caries as a result of metabolic events in the dental plaque that is related to time (35) and might be enhanced by impaired functions of saliva (36, 37). Furthermore, higher counts of mutans streptococci and lactobacilli, as well as yeasts, were revealed in poorly controlled diabetics, indicating a possible ecological shift in the composition of oral microflora (38).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results showed that increasing age and high dental plaque scores, as well as decreasing unstimulated flow rates were highly associated with increasing DMFS values, whereas no association was found with the level of HbA1c. These data confirm the existing knowledge about dental caries as a result of metabolic events in the dental plaque that is related to time (35) and might be enhanced by impaired functions of saliva (36, 37). Furthermore, higher counts of mutans streptococci and lactobacilli, as well as yeasts, were revealed in poorly controlled diabetics, indicating a possible ecological shift in the composition of oral microflora (38).…”
Section: Discussionsupporting
confidence: 88%
“…Decreased salivary flow, one of the most important determinants associated with a high caries prevalence in the present study population, could potentially explain the cariogenic changes in the oral environment of diabetics. It has previously been demonstrated that the effect of saliva on caries lesion development is very much influenced by the unstimulated flow rate and composition of saliva (36, 37). A reversible reduction of salivary secretion was found to be related to insulin deficiency and hyperglycemia in diabetics (4, 39).…”
Section: Discussionmentioning
confidence: 99%
“…Bardow et al. () showed in vivo that high unstimulated WMS concentrations of phosphate, TP and amylase were protective against caries. Finally, Garcia‐Godoy & Hicks () reported that Ca 2+ , phosphate and fluoride derived from saliva and sequestered in to the dental bio‐film are required for effective remineralization and maintenance of the enamel surface integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Some antimicrobial factors of saliva are considered to be caries protective [Amerongen et al, 2004;Bardow et al, 2005], and may have a beneficial effect on the ecology of dental plaque, but no single factor (except, perhaps, salivary flow rate) is able to affect oral health to a significant degree [Tenovuo et al, 1987;Gråhn et al, 1988;Rudney et al, 1993;Kirstilä et al, 1998]. …”
Section: Discussionmentioning
confidence: 99%